Growing up among the Looms: The Growth and Nutrition of Children Living in a Peri-Urban Environment in Kathmandu, Nepal - Moffat, Tina (My University, 1998)
This study examines the nutritional and health status of children under five years of age whose mothers are working as weavers and spinners in the carpet-making industry in Kathmandu, Nepal. The research design samples both carpet-making factories and households where the predominant mode of income generation for women is spinning wool at home for carpet manufacturers. A biocultural approach that combines quantitative and qualitative research methods - anthropometry, questionnaires and semi-structured interviews - is used to investigate the social and biological contexts of children's health and nutritional status. Although low weight-for-weight, or acute wasting, is not evident among the 283 children in this study, they are found to be moderately to severely growth stunted with poor upper arm musculature, relative to international growth standards. Similar to other children in Nepal, there is some weight loss evident in the hot and monsoon seasons compared to the cold season. Despite the fact that mothers are engaged in wage labour, both factory and home workers in this sample breastfeed for the first two to three years postpartum almost universally and therefore maternal lactation practices are not implicated in growth retardation. A synergistic interaction between low quality and quantity of weaning foods and an extremely high load of infectious disease - particularly diarrheal illnesses and gastrointestinal parasites - implicated in growth retardation. Some of the more traditional foci of child health studies such as maternal care and socio-economic status of the household are found to have little explanatory power in this research. An investigation of the peri-urban environment - the newly settled and marginal district that borders that city - points to the operation of macro environmental factors in debilitating the health of the children in this study. It is argued that an environmental health perspective constitutes the most appropriate framework for interpreting growth faltering among these children and that the lack of infrastructure in this peri-urban environment leads to poor sanitary conditions and high rates of chronic childhood infections. The research calls for increased anthropological attention to the environmental conditions that facilitate high pathogen loads among children, an area of inquiry that is often under-investigated relative to nutritional issues per se.
Keywords: Anthropology; Anthropology